Spatial behavior of hepatitis A, MMR, and varicella vaccination coverage in the state of Minas Gerais, 2020 - Gabriela Cunha Corrêa Freitas de Oliveira; Luiz Henrique Arroyo; Aline Mendes Vimieiro; Josianne Dias Gusmão; Valéria Conceição de Oliveira; Eliete Albano de Azevedo Guimarães (Revista Brasileira de Epidemiologia, 2023)
ABSTRACT Objective: To analyze the spatial behavior of hepatitis A, measles, mumps, and rubella (MMR), and varicella vaccination coverage in children and its relationship with socioeconomic determinants in the state of Minas Gerais. Methods: This ecological study investigated records of doses administered to children, extracted from the Immunization Information System of 853 municipalities in Minas Gerais, in 2020. We analyzed the vaccination coverage and socioeconomic factors. Spatial scan statistics were used to identify spatial clusters and measure the relative risk based on the vaccination coverage indicator and the Bivariate Moran Index, and thus detect socioeconomic factors correlated with the spatial distribution of vaccination. We used the cartographic base of the state and its municipalities and the ArcGIS and SPSS software programs. Results: Hepatitis A (89.0%), MMR (75.7%), and varicella (89.0%) showed low vaccination coverage. All vaccines analyzed had significant clusters. The clusters most likely to vaccinate their population were mainly located in the Central, Midwest, South Central, and Northwest regions, while the least likely were in the North, Northeast, and Triângulo do Sul regions. The municipal human development index, urbanization rate, and gross domestic product were spatially dependent on vaccination coverage. Conclusions: The spatial behavior of hepatitis A, MMR, and varicella vaccination coverage is heterogeneous and associated with socioeconomic factors. We emphasize that vaccination records require attention and should be continuously monitored to improve the quality of information used in services and research.